Enhancing Educational Processes Through Advanced Internet Didactics and Electronic Libraries: a Comprehensive Approach - Adamia, Zoia K.; Biletskyi, V. S.; Onkovych, Hanna V. (Tskhum-Abkhazian Academy of Sciences, 2024)
This paper explores the intricate application of internet didactics (wiki, film, websites, blogs, webinars) and electronic libraries in contemporary Ukrainian and Georgian university education. It demonstrates how this approach enhances the effectiveness of each internet didactic component, emphasizing that the combination of these tools is selected by educators based on specific instructional needs. Successful implementation of this synergy hinges on several conditions: access to a robust professional source base, technical infrastructure for teacher-student communication, and the creation and utilization of multimedia (video, audio, text). Both faculty and students are expected to possess advanced media literacy. Additionally, educators are encouraged not only to utilize online teaching technologies but also to actively produce educational materials such as films, websites, blogs, webinars, and Wikipedia articles. For students, the integration of research with education is crucial, facilitating closer ties between students, universities, and prospective employers. For educators, engagement in the global scholarly and pedagogical community through publications in international databases and participation in academic conferences is essential.
Keywords: complexity of educational processes; media literacy; professionally oriented media education; media didactics; wiki didactics; film didactics; website didactics; electronic libraries; higher professional education